Sosialisasi Pemanfaatan Kasgot (Bekas Maggot) BSF Sebagai Pembuatan Pupuk Organik Berbasis Rumah Tangga - Al Fath, Muhammad Thoriq; Hasibuan, Gina Cynthia Raphita; Alda, Tania; Dalimunthe, Nisaul Fadilah (CERED Indonesia Publishing, 2024)
This community service activity aims to find solutions to the problems faced by the Aisyiyah Organization mothers in Kampung Dadap, Medan, regarding the utilization of kasgot, a residue from household organic waste processing using Black Soldier Fly (BSF) maggots. The partners own agricultural land that requires additional nutrients to produce high-quality crops. Kasgot fertilizer is rich in amino acids and microorganisms that enhance soil nutrients without harming the environment. To reduce chemical fertilizer use, partners were trained to process kasgot with starch, molasses, and rice bran into solid granular organic fertilizer. The outcome is an eco-friendly, sustainable organic fertilizer.